The Capability of Image Files Cover Message in Steganography - Hanizan Shaker, Hussain (2005)
This paper is focusing on the capability of image files as cover message to send the text files. The images were classified according to their compression technique, lossless and lossy compression. The measurements are identified in order to test their capability in term of the sizeof file, the color intensity level, the integrity data and the time execution. All the measurements would be tested by using the developed tool called StegaNo. The result of the study seem to suggest BMP image as a cover message than JPEG image.